Deleuze e velhice: uma política dos encontros - Niquetti, Ricardo (2015)
This thesis is the result of a study based on the ideas of the French philosopher Gilles Deleuze. The central objective of the research was to investigate the old age as a vector to creations of itself, requiring the structuring of a policy of meetings and with the support and means, the political philosophy of Deleuze. This search begins for questions and lines for what is happening and pierces the meetings, providing approximations of what distinguish a life of all the others, ie, singling and individuation processes that express something about the ways of life of each. The adopted methodological strategy was based on a rhizome and interstitial procedure applied in the literature of the surveyed works, prioritizing the issue that is in the friction between old age as agenciadora meetings, and an implied policy in the promotion and proliferation of good meetings, and the philosophy of Deleuze support for us we slide through his conceptual thoughts, in our view, still able to attract new interference, just by virtue of everything that happens in their midst. This methodology allowed the approach of different thoughts and the development of conjugations and trials in the search for a political meetings as a possibility for other creations. The alliance between these fields enabled think old age as an event, ie, containing within it the possibility of radical transformation of existence. In addition, the research advances in the development and mapping of a Deleuzian policy meetings, which, among other things problematize contemporary lifestyles